الجَسد في القصيدة النّسوية الجزائرية المُعاصرة - قراءة في نماذج مختارة - عبيدات, الحبيب (جامعة الوادي - University of Eloued, 2021)
نسعى من خلال هذا المقال، إلى إبراز تمظهر الجسد الأنثوي في القصيدة النّسوية الجزائرية المعاصرة، كونه من أكثر المواضيع إلحاحا في الشّعر المعاصر، نظرا للتغيرات، التي عرفتها المنظومة الفكرية الجديدة، والتي أثرت بدورها على المجتمع؛ ليصبح الجسد مرحلة مهمّة في تجربة الذات النسويّة مع نفسها والآخر، لما يشتمل عليه من معان، ودلالات على صعيد النتاج الشّعري، سعتْ إليه؛ لتخترق المجهول وتتصدى للممنوع، وتخرج به إلى فضاء شعري جمالي أكثر اتساعا. وعليه فقد كان الهدف من هذه الدراسة، الكشف في ثنايا النّص الشّعري النّسوي الجزائري، عن حضور الجسد، وذلك من خلال استقراء نماذج مختارة Abstract: Through this article, we seek to highlight the manifestation of the female body in the contemporary Algerian feminist poem, as it is one of the most pressing topics in contemporary poetry, given the changes that have occurred in the new intellectual system, which in turn affected society; The body becomes an important stage in the experience of the feminine self with itself and the other, for what it contains of meanings and connotations on the level of poetic production, which it sought; To penetrate the unknown and confront the forbidden, and bring it out into a more spacious aesthetic poetic space. Accordingly, the aim of this study was to reveal, in the Algerian feminist poetic text, the presence of the body, by extrapolating selected models. Key words: appearance; the body; feminist poem; Self; Experience.
مقال
Keywords: تمظهر؛ الجسد؛ القصيدة النّسوية؛ الذات؛ التجربة